Spermophilus torosensis Özkurt et al., 2007 (Sciuridae, Rodentia) is a subjective junior synonym of Spermophilus taurensis Gündüz et al., 2007, a newly described ground squirrel from the Taurus Mountains of southern Turkey - Gündüz İslam; Jaarola, Maarit; Tez, Coşkun; Yeni̇yurt Can; Polly, P. David; Searle, Jeremy B. (Zootaxa, 2007)
Earlier this year a new species of ground squirrel (Spermophilus, Sciuridae, Rodentia) from the Taurus Mountains of southern Turkey was named independently by two research groups (Spermophilus taurensis Gündüz et al., 2007; Spermophilus torosensis Özkurt et al., 2007). Prior to these publications, the squirrels in the Taurus Mountains had been referred to the widespread species Spermophilus xanthoprymnus (Bennett, 1835). Both research groups distinguished the new species on the basis of its karyotype (2n=40), its reddish dorsal pelt, its comparatively broad, long tail, and its larger body size. Gündüz et al. (2007) further distinguished the species as being monophyletic from mitochondrial cytochrome b sequence analyses, as having diagnostic D-loop and X and Y chromosome haplotypes, and from the distinct position of the pterygoid fovea on the condylar process of the mandible. Özkurt et al. (2007) also noted spine-like posterior palatal processes, non-convergent supraorbital ridges, and reduced sagittal and lambdoidal crests as distinguishing features. Both research groups found that the species was restricted to a small area in the Taurus Mountains, including Akseki, from which the type localities were chosen (S. taurensis: village of Yarpuz in Akseki; S. torosensis: Salamut Plateau of Çaltılıçukur village in Akseki).